SMARCA4-related Coffin-Siris syndrome in newborn: a case report and literature review - Wang, Yuqian; Zhang, Li; Zhu, Jing; Yang, Liu; Wang, Chan; Zou, Ning (Frontiers in Pediatrics, 2025)
ObjectiveOur objective was to examine the clinical and genetic features of Coffin-Siris syndrome resulting from a pathogenic variant in the SMARCA4 gene.MethodsThe clinical data and molecular genetic test results of a newbron with Coffin-Siris syndrome involving a pathogenic variant in the SMARCA4 gene were retrospectively analyzed, and the related literatures were reviewed.ResultsA newborn exhibited inspiratory dyspnea following birth and developmental anomalies (coarse appearance, thick hair, long eyelashes, broad nasal tip, flat nasal bridge, thin upper lip, thick lower lip, digital anomalies, cleft palate, supraglottic laryngeal chondromalacia, stenosis of the left upper bronchus and hypotonia). Whole exome sequencing revealed a heterozygous missense variant in SMARCA4 gene (NM_003072.5 c.3127C > T, p.Arg1043Trp). Parents did not find the above pathogenic variant, which was a new pathogenic variant. In addition to our case, we also retrieved 22 cases of Coffin-Siris Syndrome in SMARCA4 gene variation, which is a congenital multi-system dysfunction syndrome characterized by abnormal appearance and developmental retardation. The common otolaryngologic features of 23 patients with CSS in SMARCA4 gene variant included palate abnormalities, feeding difficulties, ear abnormalities and hearing loss.ConclusionCoffin-Siris syndrome is a rare genetic disease inherited in an autosomal-dominated manner. It is often associated with malformations in the otorhinolaryngologic system. This case has many common features with previously reported CSS cases with pathogenic variant in the SMARCA4 gene, which further characterizes the performance of the pathogenic variant, suggesting that palatal abnormalities may be a significant feature of the genotype. For patients with developmental abnormalities, whole-genome sequencing or whole-exome sequencing is particularly important to assist diagnosis. Currently, there is no known treatment for CSS, and individuals with CSS experience various complications affecting multiple systems.